Pisatelj Milan Pugelj kot pomemben člen v kratkoprozni ustvarjalnosti z začetka 20. stoletja na Slovenskem - Bošnjak, Blanka (Jezik in slovstvo, 2004)
Part 2 of the article gives a brief comparative analysis of Pugelj's short stories and those written by two great European writers of short story - Guy de Maupassant and Anton Pavlovich Chekhov. Pugelj's attachment to naturalism was mentioned by Kocijan. Several literary historians and researchers of Pugelj's work, such as Lavrin, Pregelj, Karlin, Koblar, Mahnič, Zadravec, and more recently A. Koron, have all stressed the explict influence of Maupassant and Checkhov.
Keywords: Pugelj, Milan, 1883-1929; Slovene literature; slovenska književnost; kratka proza; literarne študije; 20.st.